Seismic response analysis on the stability of running vehicles. - Maruyama, Yoshihisa
The seismometer network of the Japanese expressway system has been enhanced since the 1995 Kobe earthquake. Using earthquake information from the instruments, the expressways are closed if the peak ground acceleration (PGA) is larger than or equal to 80 cm/s2. The aim of this regulation is to avoid secondary disasters, e.g. cars running into the collapsed sections. However, recent studies on earthquake damage have revealed that expressway structures are not seriously damaged under such level of earthquake motion. Hence, we may think of relaxing the regulation of expressway closure. But before doing this, it is necessary to examine the effects of shaking to automobiles since the drivers may encounter difficulties in controlling their vehicles and traffic accidents may occur. In this study, a vehicle was modelled with a six degree of freedom system and its responses were investigated with respect to PGA, peak ground velocity (PGV) and Japan Meteorological Agency (JMA) seismic intensity using five ground motion records. It was observed that the response of the vehicle shows a larger amplitude for the record that has larger response spectrum in the long period range compared to other records. However, similar response amplitudes of the vehicle were observed for all the records with respect to the JMA seismic intensity. The response characteristics of the vehicle model may be very useful for decision making regarding the relaxation of the expressway closure under seismic motion.
Keywords: Seismic motion; Vehicle model; Seismic response analysis; Vehicle response; Expressways